Conditioned media from (pre)adipocytes stimulate fibrinogen and PAI-1 production by HepG2 hepatoma cells - Faber, D R; Kalkhoven, E; Westerink, J; Bouwman, J J; Monajemi, H M; Visseren, F L J (Nutrition & diabetes, 2012)
Background: Obesity is associated with a prothrombotic state, which may contribute to the increased risk of thrombotic events. Objective: To assess the effects of (pre)adipocyte-derived adipokines on fibrinogen, plasminogen activator inhibitor-1 (PAI-1) and tissue factor (TF) production by hepatocytes. Methods: HepG2 hepatocytes were incubated with conditioned media (CM) derived from preadipocytes and adipocytes, which had been untreated or prestimulated with tumor necrosis factor (TNF)-α, interleukin (IL)-1β or IL-6. After 24 h, supernatants and cell lysates were harvested for measurement of fibrinogen, PAI-1 and TF. Results: (Pre)adipocyte CM significantly enhanced the production of PAI-1 by HepG2 cells 2.5- to 4.4-fold. CM from cytokine-stimulated (pre)adipocytes significantly induced fibrinogen secretion 1.5- to 4.2-fold. TF production was not affected by the CM. After specific depletion of TNF-α, IL-1β or IL-6 from the CM, IL-6 was shown to be the most prominent stimulus of fibrinogen secretion and IL-1β of PAI-1 secretion. In addition, fibrinogen, PAI-1 and tissue factor production was evaluated by direct stimulation of HepG2 cells with TNF-α, IL-1β or IL-6. IL-6 enhanced fibrinogen synthesis 4.3-fold ( P <0.01), whereas IL-1β induced PAI-1 production 5.0-fold ( P <0.01). Gene expression analyses showed that TNF-α and IL-1β stimulate the adipocyte expression of TNF-α, IL-1β and IL-6. Cytokine stimulation of adipocytes may thus have induced an inflammatory response, which may have stimulated fibrinogen and PAI-1 production by HepG2 cells more potently. Conclusions: SGBS (pre)adipocytes release cytokines that increase the production of fibrinogen and PAI-1 by HepG2 cells. IL-6 and IL-1β produced by (pre)adipocytes were the strongest inducers of fibrinogen and PAI-1 secretion, respectively.